2014
DOI: 10.1177/0091026014530270
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Motivation and Institutional-Occupational Motivations Among Undergraduate Students and ROTC Cadets

Abstract: Given the current fiscal climate, budgetary pressures may have important implications for recruitment and retention of military personnel. In response to this issue, we join two literatures to study motivational differences in undergraduate college students and Reserve Officer Training Corps (ROTC) cadets: Moskos’ Institutional and Occupational (I-O) enlistment motivation model and Kim et al.’s revised Public Service Motivation (PSM) scale. We survey ROTC cadets and undergraduates at a mid-size public universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…The concept is connected to a range of work attitudes and behaviors (Bright 2007(Bright , 2008(Bright , 2013Caillier 2016;Gould-Williams et al 2015;Kim 2012). While there are studies that have explored the connection that military experience has to the level of PSM of undergraduate students (Ngaruiya et al 2014) and deployed military personnel (Braender and Andersen 2013), there are no studies that were found that explored the influence of military experience on the level of PSM among employees in civilian work organizations.…”
Section: Comparative Research In Civilian Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept is connected to a range of work attitudes and behaviors (Bright 2007(Bright , 2008(Bright , 2013Caillier 2016;Gould-Williams et al 2015;Kim 2012). While there are studies that have explored the connection that military experience has to the level of PSM of undergraduate students (Ngaruiya et al 2014) and deployed military personnel (Braender and Andersen 2013), there are no studies that were found that explored the influence of military experience on the level of PSM among employees in civilian work organizations.…”
Section: Comparative Research In Civilian Organizationsmentioning
confidence: 99%
“…Secondly, the transition of individuals from the military into civilian life should be a major focus for public management scholars. Yet, research on this issue has been largely absent from the public management literature (Charbonneau et al 2020;Ngaruiya et al 2014;Taylor et al 2013;Teclaw et al 2016). More research will help direct future research and hypotheses on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some studies report undesirable effect of PSM such as increasing employee stress and withdrawal (Giauque et al, 2012; Quratulain & Khan, 2013). The assumptions that individuals having high PSM tend to self-select for public service employment and all public service organizations always conduct their work according to the norms of PSM, are two contestable assumptions (Coursey, Yang, & Pandey, 2012; Kjeldsen & Andersen, 2013; Ngaruiya, Velez, Clerkin, & Taylor, 2014). Similarly, with the ubiquity of cross-sectional studies it is not possible to resolve the issue of causality, where some studies suggest that organizational factors have limited influence on developing employee values (Kim et al, 2013; Wright & Pandey, 2008), whereas others suggest that organizational characteristics do affect PSM (Gould-Williams, Mostafa, & Bottomley, 2013).…”
Section: Organizational Work Environment and Psmmentioning
confidence: 99%
“…A partir do estudo de Kim e Vandenabeele (2010), Kim et al (2013) realizaram um refi namento e esclarecimento das dimensões operacionais da MSP, dando origem a um novo instrumento com 4 dimensões e 16 itens concebidos e/ou redefi nidos: atração para o serviço público (ASP), comprometimento com valores públicos (CVP), compaixão (COM) e autossacrifício (AS). Esse novo instrumento ampliou a compreensão sobre a temática e foi adotado em estudos posteriores (WRIGHT; CHRISTENSEN; ISETT, 2013;NGARUIYA et al, 2014;DESMARAIS;GAMASSOU, 2014;PRYSMAKOVA, 2016;KIM, 2016). Posteriormente, ressalta-se que o estudo de Kim (2017) logrou melhores propriedades psicométricas para a dimensionalidade proposta por Kim, et al (2013), no contexto coreano, a partir da revisão operacional de itens.…”
unclassified